Pengembangan Tanbih Suryalaya Berbahasa Arab: Bahan Ajar Pendidikan Bahasa Arab berbasis Pembangunan Berkelanjutan - Syakir, Mukhlis; Baroroh, Umi (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
Education based on sustainable development is an idea that has long been initiated by UNESCO in facing global challenges in the 21st century. As a result of previous development that did not pay attention to sustainability in terms of economic, social and environmental aspects. We can see the impact on environmental damage, economic inequality, fractured social relations, and other problems. Actually, if we want to examine cultural and religious heritages in depth. These impacts should not occur massively or at least can be controlled. Among the cultural heritage that contains the value of sustainable development is the Tanbih Suryalaya Text, which is still often recited by its followers. Therefore, this article will attempt to develop the Tanbih text, which is still in Sundanese, into Arabic. Then make it as a teaching material for Arabic Language Education based on sustainable development through a descriptive qualitative approach method with literature study sources. The result of this research is an Arabic learning model that utilizes the Suryalaya tanbih text.